Stress and Coping in Youth With Spina Bifida: A Brief Longitudinal Study in a Summer Camp Setting - Ohanian, Diana M.; Kritikos, Tessa K.; Clark, Olivia E.; Shirkey, Kezia C.; Starnes, Meredith; Holmbeck, Grayson N. (Frontiers in Psychology, 2021)
Introduction: It is well established that youth with chronic conditions experience elevated levels of stress; the manner in which they respond to or cope with this stress is likely to impact both health and psychosocial outcomes. The current study examined stress and coping in youth and young adults with spina bifida (SB) using the Response to Stress Questionnaire-SB version (RSQ-SB; Connor-Smith et al., 2000). Methods: Data were collected as part of a camp-based psychosocial intervention for children (ages 7-13), adolescents (ages 14-19), and young adults (ages 20-38) with SB. Participants completed the RSQ-SB as well as questionnaires assessing demographics and condition severity. Data were collected prior to camp (T1) and 1 month (T2) after camp ended. Self-report data were collected from adolescents and young adults; parents of children and adolescents reported on their child’s stress and coping. Ratios of primary control coping, secondary control coping, disengagement coping, involuntary engagement, and involuntary disengagement coping were calculated. Descriptive statistics and t-tests were utilized to describe coping and stress responses and to determine potential change over time. T-tests were also used to compare youth and parent reported coping styles with those of youth with type 1 diabetes (T1D) and sickle cell disease (SCD). Associations between demographic/disease factors and coping styles were also examined. Results: Parent and youth report indicated that youth with SB tend to use primary control coping. Youth with SB use more primary control coping and less disengagement coping compared to youth with SCD and youth with T1D. Few significant changes in coping were found between T1 and T2. IQ and socioeconomic status were significantly associated with coping styles. Conclusion: Youth with SB use more primary control coping compared to other coping methods and as compared to other pediatric populations. Future studies should examine mechanisms by which primary control coping is advantageous for youth with SB. Future interventions should be more focused on promoting adaptive coping behaviors and be tailored to developmental age and access to resources.